Manuscritos hebraicos em Portugal - Tiago Moita (Medievalista)
This paper makes the first comprehensive inventory of Hebrew manuscripts in public libraries and state archives in Portugal. The inventory includes the identification and location of the manuscripts and presentation according to their contents; following a thorough codicological and paleographical analysis, their origin and probable date of production is also discussed. The circumstances of acquisition or entry of the volumes into the libraries are also considered. In many cases, the results obtained allow the update of the existing information about these manuscripts in the catalogs of the libraries where the volumes are held.